Design and analysis of single phase pure sine inverter based on phase locked loop - Sisuk, Noppadon; Suphramit, Suphawadee; Kaewpoonsuk, Anucha; Wardkien, Paramote (My University, 2016)
This article proposes the new technique of the PWM oscillation based on phase locked loop that controls the inverter. The PWM works together with push-pull where it is connected to the step-up transformer. The advantages of proposed technique are that the PWM circuit is non-complicated of structure and that the PWM circuit can prevent from a noise signal. In addition, a carrier frequency can be adjusted at a frequency running with the VCO of a phase locked loop. The PWM output which is obtained from the push-pull inverter has high symmetry voltage. Ultimately, the PWM is passed through the LC low pass filter where high pure sine wave signal occurs. As a result, the total harmonic distortion (THD) is decreased which is equal to 2.27%. Due to the related proposed technique, the output voltage regulation is improved and the dynamic response ofa step load change is also improved.
Keywords: Phase locked loop; Pulse width modulation; Pure sine wave inverter